MEMAHAMI PENGUNGKAPAN DIRI INDIVIDU LESBIAN GAY BISEXUAL DAN TRANSGENDER (LGBT) DI MEDIA SOSIAL - Rindiana Kiswari; S. Rouli Manalu; Turnomo Rahardjo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The increasing frequency of LGBT individuals expressing themselves in the midst of stigma and discrimination against LGBT raises questions about how LGBT individuals use social media as a platform to express themselves, manage privacy, describe the experience of expressing themselves online, feedback and its impact on their behaviour in real life. This will be examined using the concepts of Self-disclosure, Communication Privacy Management and Stigma Theory. This research is a qualitative study using Interpretive Phenomenology Analysis (IPA) with in-depth interview techniques. The researcher found that the characteristics of social media platforms (anonymity and LGBT-friendly of Twitter, Instagram's interesting pictures and videos, and Tiktok as a youth social media with a wide range) become criteria in choosing and managing self-disclosure on social media. Friending action through the block, hide, close friend, implicit caption features is an effort to manage boundaries. Forms of self-disclosure include sexual orientation (coming out, romance, sexual life, coming out in RL, roles in relationships) and campaigns/advocacy (Self-acceptance', 'Stop bullying', 'Gender and Sexual Diversity', 'Human rights' and LGBT Culture). LGBT individuals choose to focus on positive responses only. Then there is the negotiation of LGBT identity with religion related to internalised stigma after self-disclosure. There is a good feeling of being famous. Furthermore, turbulence in the management of private information on social media makes informants review and make new rules in expressing themselves. Researchers suggest that LGBT individuals use the features provided by social media to the fullest to achieve commonality of meaning and reduce the possibility of being stigmatised due to the lack of commonality of meaning. Researchers suggest studying the management of private information of LGBT individuals on social media with various levels of popularity in future research.